MINAT BELI KONSUMEN DI BAKSO KOTA CAK MAN MAGELANG - Erwin Setiawan; Steven (Akademi Pariwisata NHI Bandung, 2021)
This study aims to determine buying interest in Bakso Cak Man Magelang. In this paper, the research method that the author uses is descriptive. Data collection techniques were carried out by distributing questionnaires, observations, interviews and literature studies. While the technique of data analysis using a Likert scale. Based on the results of the research, it can be seen that in general, buying interest has not been achieved. The problems in the research: 1) How is consumer attention to Meatballs in Cak Man Magelang, 2) How is consumer interest in Meatballs in Cak Man Magelang? and 3) What is the consumer's desire for Meatballs in Cak Man Magelang City?. 4) What are the consumer's actions towards the Cak Man Magelang City Meatballs?. Suggestions given for this research are 1) Cak Man City Meatballs, Magelang, need to develop a variety of food and beverage products. 2) Cak Man Magelang City Meatballs are expected to further expand advertising and promotions to increase the number of customers buying at Cak Man Magelang City Meatballs. 3) Cak Man City Meatballs are expected to evaluate effective marketing strategies because consumer demand tends to decline. 4) There are many aspects that still need to be improved and maximized in the future. It also has a positive influence on the company if customer satisfaction is met.